The contribution of the population of the Ulyanovsk region to achieving victory in the Great Patriotic War - Fedorova S. I., Provalova E. V. (University as a factor of Modernization of Russia: History and Prospects (to the 55th anniversary of the I.N. Ulyanov ChSU), 2024)
the article is dedicated to certain events in the military history of the Ulyanovsk region, showing the contribution of the region's residents to the victory over Nazi Germany. It presents an example of heroism and patriotism of Ulyanovsk residents – our fellow countrymen. The authors outline the important role of the Volga region, specifically the Ulyanovsk region in achieving victory due to its specific historical situation, geographical and strategic location. Ulyanovsk is the city where many enterprises evacuated from other cities of the country were situated: Moscow, Vitebsk, etc. The article describes the labour heroism that created the conditions for turning our region into a powerful military centre. The work allows to expand and consolidate knowledge about the history of the Ulyanovsk region in the young generation, to form a sense of civic consciousness.
Keywords: Великая Отечественная война; патриотизм; Great Patriotic War; Patriotism; героизм; Отечество; Fatherland; героическое прошлое; heroism; heroic past; подвиг; молодое поколение; feat; ульяновцы; Ulyanovsk residents; younger generation